Primary retroperitoneal ectopic pregnancy - Reyna-Villasmil, Eduardo (2023)
Ectopic pregnancy accounts for 1.5%-2% of all pregnancies and is a common causeof pregnancy-related mortality during the first trimester. The most common locationis the fallopian tube and less than 2% are abdominal pregnancies. Retroperitonealectopic pregnancy is an extremely rare type with a rather complex pathogenesis.This unusual location has a high risk of life-threatening complications. Early diagnosisis difficult because of the inability to differentiate signs, symptoms, chorionicgonadotropin concentrations, and imaging with ectopic pregnancies from unusuallocations, such as the retroperitoneum. In addition, it is necessary to be carefulwith the diagnosis of these cases when the most common sites of appearance donot present alterations. Treatment consists of removal of trophoblastic tissue bylaparotomy or laparoscopy. A case of primary retroperitoneal ectopic pregnancy ispresented.